Factors associated with parasympathetic activation following exercise in patients with rheumatoid arthritis: a cross-sectional study. Issue 1 (December 2016) - Osailan, Ahmad; Metsios, George; Rouse, Peter; Ntoumanis, Nikos; Duda, Joan; Kitas, George; Veldhuijzen van Zanten, Jet
Abstract Background Patients with rheumatoid arthritis (RA) have an increased risk for cardiovascular disease (CVD) with poor parasympathetic function being implicated as an underlying factor. Factors related to parasympathetic function, commonly assessed by heart rate recovery (HRR) following maximal exercise, are currently not known in RA. We aimed to explore the association between HRR with CVD risk factors, inflammatory markers, and wellbeing in patients with RA. Methods Ninety-six RA patients (54.4 ± 12.6 years, 68 % women) completed a treadmill exercise test, during which heart rate (HR) was monitored. HRR1 and HRR2 were defined as the absolute change from HR peak to HRR 1 min post HR peak and 2 min post HR peak, respectively. Cardiorespiratory fitness, CVD risk factors, and serological markers of inflammation were measured in all patients. The Framingham Risk Score (FRS) was used as an assessment of global risk for CVD events, and wellbeing was assessed by questionnaires. Results Mean HRR1 and HRR2 were 29.1 ± 13.2 bpm and 46.4 ± 15.3 bpm, respectively. CVD risk factors as well as most inflammatory markers and measures of wellbeing were inversely correlated with HRR1 and HRR2. Multivariate regression analyses revealed that 27.9 % of the variance in HRR1 and 37.9 % of the variance in HRR2 was explained collectively by CVD risk factors, measures of inflammation, and wellbeing (p = 0.009, p = 0.001 respectively), however no individual measure was independently associated with HRR1 or HRR2. Conclusion Parasympathetic activation was associated with overall CVD risk, arthritis-related burden and wellbeing in patients with RA. Trial Registration [Exercise, cardiovascular disease and rheumatoid arthritis, ISRCTN04121489 ]